2013
DOI: 10.4049/jimmunol.1301885
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Secreted by Human Placenta Carry Functional Fas Ligand and TRAIL Molecules and Convey Apoptosis in Activated Immune Cells, Suggesting Exosome-Mediated Immune Privilege of the Fetus

Abstract: Apoptosis is crucially important in mediating immune privilege of the fetus during pregnancy. We investigated the expression and in vitro apoptotic activity of two physiologically relevant death messengers, the TNF family members Fas ligand (FasL) and TRAIL in human early and term placentas. Both molecules were intracellularly expressed, confined to the late endosomal compartment of the syncytiotrophoblast, and tightly associated to the generation and secretion of placental exosomes. Using immunoelectron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
243
2
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(265 citation statements)
references
References 63 publications
10
243
2
10
Order By: Relevance
“…55 Some papers have reported that microRNA-containing or Fas ligand-expressing exosomes from Tregs or other tissues could mediate effector T-cell apoptosis. [56][57][58] Taken together, CD4 1 VEGFR1 high T-cell-mediated suppression might be exerted in various ways depending on the microenvironment, so that further studies to identify soluble factor(s) responsible for the suppressive activity should be considered under various circumstances. IBD is a chronic and relapsing inflammatory disorder and one of the CD4 1 T-cell-mediated autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…55 Some papers have reported that microRNA-containing or Fas ligand-expressing exosomes from Tregs or other tissues could mediate effector T-cell apoptosis. [56][57][58] Taken together, CD4 1 VEGFR1 high T-cell-mediated suppression might be exerted in various ways depending on the microenvironment, so that further studies to identify soluble factor(s) responsible for the suppressive activity should be considered under various circumstances. IBD is a chronic and relapsing inflammatory disorder and one of the CD4 1 T-cell-mediated autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the direct quantification of placenta-derived exosomes from total purified exosomes using PLAP as a placenta-specific marker has been achieved. [79][80][81][82][83][84][85] In contrast to immunocapture methods, this method eliminates inaccuracies attributed to the lower exosomal yield obtained using immunocapture techniques. However, the direct quantification of placentaderived exosomes in maternal circulation is largely dependent on the purity of the exosomal fraction.…”
mentioning
confidence: 99%
“…Exosomes usually contain a variety of molecules that are native to the originating cell and enriched with endosome-associated protein markers, such as tetraspanins (CD63, CD81, CD82, CD9, CD37), HSP70, RAB proteins, ALIX, TSG101, endocytic proteins, and cell-specific proteins, which provide information regarding their cellular origin. 95 Pregnancyassociated exosomes have been found to contain a number of membrane-bound protein markers, such as NKGD2 ligands, 96 FasL, 82,83 TRAIL, 82 and syncytin 1, 97 which suggests that placenta-derived exosomes play a key role in maintaining maternal-fetal tolerance (Figure 4). Other specific pregnancy-associated exosomal proteins, such as TGFβ, indicate that placenta-derived exosomes are involved in the control of STB growth, proliferation and differentiation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is of interest to note that EVT cell invasion is increased by both gal-1 (Kolundzic et al, 2011b) and EVs from cytotrophoblast cells grown in a hypoxic environment (Salomon et al, 2013). Both gal-1 (Blois et al, 2007;Tirado-Gonzalez et al, 2013) and placental EVs (Stenqvist et al, 2013;Mincheva-Nilsson and Baranov, 2014;Tannetta et al, 2014) are involved in immunoregulation during pregnancy. As for gal-3 and gal-8, their role in trophoblasts is still unresolved.…”
Section: Discussionmentioning
confidence: 99%